Pemberdayaan Kelompok Wanita Wirausaha Melalui Pengolahan Jantung Pisang dan Ikan Lele Menjadi Abon di Kabupaten Nganjuk - Suwinda Fibriani; Fitri Krismiratsih; Khomsatun Ni’mah; Vera Amalia S; Dhiva Singgih (Journal of Community Development, 2025)
This Community Service Activity aims to empower women entrepreneurs in Nganjuk Regency through training in processing banana heart and catfish into shredded fish. This program was initiated to improve the skills and economic income of women's groups, as well as to optimize the utilization of abundant but underutilized local resources. The criteria for women entrepreneurs who participate in this program are 1) women entrepreneurs who are members of the Nganjuk Regency UMKM, 2) have an interest in catfish processing and 3) women entrepreneurs who play an active role in developing the creative economy. The methods used include analysis of needs problems, technical training in raw material processing, business management, and shredded fish product marketing strategies, monitoring and evaluation. This activity was carried out at the Village Hall of Kauman Village, Nganjuk District, Nganjuk Regency. The results of this activity showed a significant increase in technical skills, business knowledge, and income of the women's groups involved. In addition, participants were able to learn business management and marketing strategies that helped them develop their businesses professionally and sustainably.. The success of this activity confirms that appropriate training and empowerment can produce sustainable positive changes and become a model that can be applied in other areas.